Broadband internet subscription rates and opioid prescribing via telemedicine during the COVID‐19 pandemic. Issue 4 (27th February 2022) - Oyler, Douglas R.; Slavova, Svetla; Freeman, Patricia R.; Huang, Zhengyan; Talbert, Jeffery; Walsh, Sharon L.; Westgate, Philip M.
Abstract: Purpose: In response to the COVID‐19 pandemic, the US DEA allowed controlled substance prescriptions to be issued following a telemedicine encounter. This study evaluated changes in opioid prescribing in Kentucky counties with low and high rates of broadband subscription before, during, and after a series of statewide emergency declarations that may have affected health care access. Methods: The study used the prescription drug monitoring program to analyze records of opioid analgesic prescriptions dispensed to opioid‐naïve individuals in high (N = 26) and low (N = 94) broadband access counties during 3 periods: before a state of emergency (SOE) and executive order (EO) limiting nonemergent health care services (January 2019‐February 2020), while the EO was active (March‐April 2020), and after health care services began reopening (May‐December 2020). Marginal generalized estimating equations‐type negative binomial models were fit to compare prescription counts by broadband access over the 3 periods. Findings: Rates of opioid dispensing to opioid‐naïve individuals decreased significantly during the EO, but increased nearly to pre‐SOE levels after health care services began reopening. Dispensing rates in low broadband counties were higher than those in high broadband counties during all time periods, although these differences were negligible after adjusting for potential confounders. During the EO, prescriptions were written for longer days' supply in both county types. Conclusions: The overall dramatic reduction in opioid prescribing rates should be considered when evaluating annual opioid prescribing trends. However, broadband subscription rate did not appear to influence opioid prescriptions dispensed in Kentucky during the EO.